Can bioelectrical stimulation favor orthodontic treatment? A randomized clinical trial to evaluate tooth movement, patient-centered, and inflammatory biomarker outcomes - Barsi, Paula Caroline; Santamaria, Mauro Pedrine; Casarin, Renato Corrêa Viana; Stolf, Camila Schmidt; Vedovello, Sílvia Amélia Scudeler; Zuppardo, Marcelo Lelis [UNESP]; Bautista, Cristhian Reynaldo Gomez [UNESP]; Zaniboni, Ewerton; Mathias-Santamaria, Ingrid Fernandes; Santamaria-Jr, Milton [UNESP] (Elsevier, 2023)
Exogenous bioelectrical stimulation (BES) modulates the bone remodeling. This study aimed to evaluate the effect of BES on clinical, patient-centered, and inflammatory biomarker outcomes of orthodontic tooth movement (OTM). A randomized clinical trial (n = 28) matched for sex (8 men and 6 women in each group) were divided into the control group with a sham device (ie, mouthpiece turned off): OTM + SHAM (mean age of 19.4 years), and the test group: OTM + BES (mean age of 20.1 years). Orthodontic alignment was performed with 0.012-in, 0.014-in, and 0.016-in nickel-titanium wires. BES (10 μA/5 min) was applied immediately after each wire installation, after 48 hours, and once a week until the next wire. The canine-to-canine crowding and little dental irregularity index in the mandibular arch were analyzed. Pain perception was measured at 0, 24, 48, and 72 hours after replacement of the 0.014-in and 0.016-in wires. Inflammatory biomarkers were assessed 48 hours after the replacement of the 0.014-inch wire in gingival fluid. The crowding difference was greater in the OTM + BES than in the OTM + SHAM after 2- and 3-month evaluations and the little index was lower in OTM + BES after 3 months of treatment. During the 0.014-in wire alignment, patient pain perception was lower in the OTM + BES than in the OTM + SHAM at 24 and 48 hours, and lower after 24 hours in the 0.016-in wire alignment. BES treatment increased IL-6 and decreased IL-10 levels in gingival fluid after 48 hours of dental alignment. Exogenous bioelectrical stimulation can accelerate initial OTM, decrease patient pain perception, and modulate inflammatory biomarkers.